Rapid high‐resolution melting method to identify human leukocyte antigen‐G (HLA‐G) 3′ untranslated region polymorphism +3142C/G (rs1063320). Issue 11 (3rd October 2021) - Ben Salah, Hamza; Jelassi, Refka; Zidi, Ines; Ben Amor, Amor; Bizid, Sondes; Ammi, Radhia; Guizani, Lamia; Bouratbine, Aida; Aoun, Karim; Chelbi, Hanen
Abstract: Background: HLA‐G is a non‐classical class I gene of the human Major Histocompatibility encoding molecules with immune‐modulatory properties. Expression of HLA‐G is being largely studied in pathological conditions, such as tumors, viral infections, inflammation, and autoimmune diseases, grafted tissues, among others. HLA‐G +3142C/G (rs1063320: dbSNP database) polymorphism is located in 3′ UTR of HAL‐G and plays a key role in determining the magnitude of gene and protein expression. The detection of HLA‐G +3142C/G polymorphism in the most published report is done through polymerase chain reaction followed by enzymatic digestion. Therefore, it is so interesting to develop a rapid and sensitive assay to genotype HLA‐G +3142C/G polymorphism. High‐resolution melt analysis (HRM) is a technology that is based on the analysis of the melting profile of PCR products through gradual temperature increase. The aim of this work is to apply high‐resolution melt method for genotyping the HLA‐G +3142C/G polymorphism. Methods: DNA from 118 individuals was extracted from whole blood with QIAamp ® DNA blood mini kit (Qiagen, Germany). Primer couple was designed using Primer 3 online tools so as to have only one SNP in the target sequence for high HRM efficiency. Positive Controls were identified using DNA sequencing and used as reference when assigning genotypes for trial samples. Results: We were able to recognize the three genotypes with similar accuracy than DNA sequencing using high resolution melting method. Hardy‐Weinberg equilibrium test shows that our population is in equilibrium for the studied SNP. Genotypes frequencies of +3142C/G polymorphism in Tunisian general population are 0.475 for heterozygote G/C, 0.186 for homozygote G/G and 0.339 for homozygote C/C. Conclusion: HRM is a cost‐effective method suitable for SNP genotyping. Abstract : HLAG SNPs molecular identification and QPCR‐HRM analysis.